Citizenship, politics and National identity in Uruguay: some genealogical sketches - Gallardo, Javier (EUNOMÍA. Revista en Cultura de la Legalidad, 2018)
This paper reconstructs some of the foundational discourses of a citizen’s self-understanding view of the national identity in Uruguay, revealing two representative moments of the set of ideas and the political language about the Uruguayan citizenship and its ascendancy in the political trajectories of the country. One of them, identified with the political component of a monolithic citizenship or rifted from society, informed by an original identity gap and by the imaginary of a republican self-government. The other, animated by various speeches that, regarding to the political integration of foreigners, will come to privilege the social or cultural attributes of citizens and their aptitudes to reproduce a stable political order, thus giving a new standardized turn to citizen identities. Although these genealogical reconstructions make it possible to appreciate the conceptual connections of these languages with the conventional theories of citizenship, they also reveal some persistent deficits in the pluralistic and democratic self-identification of Uruguayan politics.